2010
DOI: 10.1111/j.1439-0396.2010.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coated and non‐coated fatty acid supplementation on broiler chickens experimentally infected with Campylobacter jejuni

Abstract: The aim of this study was to examine whether and to what extent the supplementation of feed with a coated or non-coated mixture of fatty acids (caprylic and capric acid) affects broiler chickens experimentally infected with Campylobacter jejuni. The study was carried out using 48 chickens divided into four experimental groups. Throughout the whole rearing period (1-42 days), the chickens were fed a diet supplemented with 0.25% caprylic and capric acid (1:1), coated or non-coated. At the age of 14 and 28 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…jejuni by 2 log 10 after 10 days of supplementation in both the coated and noncoated form (Molatová et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…jejuni by 2 log 10 after 10 days of supplementation in both the coated and noncoated form (Molatová et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the antibacterial potency of MCFA is believed to exceed that of short-chain fatty acids (SCFA; Hermans et al, 2010). Several recent studies described the evaluation of in-feed SCFA (formic, acetic, propionic, and butyric acid) and MCFA (caproic, caprylic, capric, and lauric acid) to reduce (Hermans et al, 2010;Molatova et al, 2011;Solis de los Santos et al, 2010) or prevent (Sohs de los Santos et al, 2008;Van Deun et al, 2008) cecal Campylobacter colonization in broilers; however, inconsistent results have been reported. Alternatively to their in-feed use, MCFA can be administered through the drinking water as well, but studies using water applications of MCFA are scarce.…”
Section: Introductionmentioning
confidence: 95%
“…However, feed intake was suppressed and cecal counts of Campylobacter at 42 days were not reduced. A similar, earlier, study (Molatová et al, 2011) used a capric/caprylic acid mix in feed from 1-day-old and oral challenge (with the same dose and strain as the previous study) at 2 and 4 weeks. This study reported a reduction in cecal Campylobacter counts of around two log 10 units at 6 weeks of age, irrespective of whether the acids were coated with a vegetable oil preparation or not.…”
Section: Acidic Feed Additivesmentioning
confidence: 95%